Pengaruh Disiplin Kerja dan Motivasi terhadap Kinerja Pegawai pada Perusahaan Daerah Air Minum Tirta Amerta Kabupaten Blora - Dhea Karina Fitri; Sudharto P Hadi (Jurnal Ilmu Administrasi Bisnis, 2016)
The issue of this study is not all of employee increased their performance as time goes by. It shown from the sum of complains and the rate of employee absent in PDAM Tirta Amerta Blora Regency which having a quite significant fluctuation in each month of 2014 and 2015.Based on Rahmatullah (2003) in Setiyawan nad Waridin (2006) performance is influenced by 3 base factors, which one of them is individual factor which include work disipline and motivation.The aim for this study is to examine the effect of work discipline and motivation toward employee’s work. This study using explanatory research method. Population of this study are all of the employee of PDAM Tirta Amerta Blora Regency, with total 103 employee, using sampling method of Slovin 10% formula, thus the final sample used are 51 employees. The collection of data technique is using questionnaire through the test of validity and reability, advance interview and observation. Data is analyzed using linear and multiple regression, correlation coefficient, determination coefficient, t- test and f-test using SPSS ver. 20 program.The result of this study show that work discipline toward work employee have intermediate correlation with rate 0,476. The determination coefficient (R2) of work discipline to employee’s work are 22,7%. Motivation toward employee’s work have intermediate correlation with rate 0,576. The determination coefficient (R2) of work motivation to employee’s work are 33,1%. Simultanously, work discipline and motivation give positive effects toward employee’s work with F count (12,901) > F table (3,187) with signification 0,000 < 0,05. The conclusion of this study is work discipline and motivation give positive effect toward PDAM Tirta Amerta Blora Regency employee’s workRecommendation for the company to improving employee’s work, company need to improve their attention toward employee work discipline and motivation thus it can improbe employee’s work..